Immune-related gene signature associates with immune landscape and predicts prognosis accurately in patients with Wilms tumour - Tian, Xiao-Mao; Xiang, Bin; Jin, Li-Ming; Mi, Tao; Wang, Jin-Kui; Zhanghuang, Chenghao; Zhang, Zhao-Xia; Chen, Mei-Ling; Shi, Qin-Lin; Liu, Feng; Lin, Tao; Wei, Guang-Hui (Frontiers in Immunology, 2022)
Wilms tumor (WT) is the most common kidney malignancy in children. Chemoresistance is the leading cause of tumor recurrence and poses a substantial therapeutic challenge. Increasing evidence has underscored the role of the tumor immune microenvironment (TIM) in cancers and the potential for immunotherapy to improve prognosis. There remain no reliable molecular markers for reflecting the immune landscape and predicting patient survival in WT. Here, we examine differences in gene expression by high-throughput RNA sequencing, focused on differentially expressed immune-related genes (IRGs) based on the ImmPort database. Via univariate Cox regression analysis and Lasso-penalized Cox regression analysis, IRGs were screened out to develop an immune signature. The accuracy and prognostic value of this signature were validated by using Kaplan-Meier curves, time-related ROC analyses, univariate and multivariate Cox regression analyses, and nomograms. Furthermore, we found that the immune signature could reflect the immune status and immune cell infiltration character played in the tumor microenvironment (TME) and showed significant association with immune checkpoint molecules, indicating that the poor prognosis may be partially explained by its immunosuppressive TME. Remarkably, TIDE, a computational method to model tumor immune evasion mechanisms, showed that this signature holds great potential for predicting immunotherapy responses in TARGET-wt cohort. To decipher the underlying mechanism, GSEA was applied to explore enriched pathways and biological processes associated with immunophenotyping and Connectivity map (CMap) analysis for drug exploration. Finally, four candidate immune genes were selected, and their expression levels in WT cell lines were monitored via qRT-PCR. Taken together, we established a novel immune signature that may serve as an effective prognostic signature and predictive indicator for immunotherapy response in patients with WT. The study may shed light on treatment strategies for WT patients from an immunological perspective.